Implementasi Sistem E-Business pada UMKM: Tantangan dan Peluang - Anggi Pranata; Hastiani Nasution; Zaskya Azhar Azaddin; Nurbaiti Nurbaiti (Trending: Jurnal Manajemen dan Ekonomi, 2025)
This study examines the impact of implementing E-Business systems on Micro, Small, and Medium Enterprises (UMKM) in Indonesia, highlighting the challenges and opportunities presented by the digital era. The aim of this research is to identify the benefits of E-Business for UMKM, assess the barriers to its adoption, and propose strategies for effective implementation. A qualitative research method was employed, utilizing literature review and thematic analysis to gather relevant data from various sources. The findings indicate that E-Business can significantly enhance market access, operational efficiency, and customer satisfaction for UMKM. However, challenges such as limited knowledge and technological resources hinder effective implementation. This study concludes that UMKM should invest in training programs to improve digital skills and collaborate with the private sector to enhance digital infrastructure. It is recommended that UMKM focus on creative content development and engage with younger generations for effective marketing through social media.